2014
DOI: 10.1172/jci71640
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic mechanisms responsible for levodopa-induced dyskinesias in Parkinson’s disease patients

Abstract: Levodopa-induced dyskinesias (LIDs) are the most common and disabling adverse motor effect of therapy in Parkinson's disease (PD) patients. In this study, we investigated serotonergic mechanisms in LIDs development in PD patients using 11 C-DASB PET to evaluate serotonin terminal function and 11 C-raclopride PET to evaluate dopamine release. PD patients with LIDs showed relative preservation of serotonergic terminals throughout their disease. Identical levodopa doses induced markedly higher striatal synaptic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
186
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 217 publications
(195 citation statements)
references
References 39 publications
7
186
1
1
Order By: Relevance
“…Although amantadine was the result of a serendipitous discovery, increasing evidence points to the serotonergic system as a key player in the induction and expression of levodopa-induced dyskinesia (LID) in both patients with Parkinson's disease (Bonifati et al, 1994;Politis et al, 2014) and animal models of the disorder (Carta et al, 2007;Muñ oz et al, 2008). Studies in rat and primate models of Parkinson's disease have demonstrated that the serotonergic system is a major source of striatal levodopa-derived dopamine release (Carta et al, 2007;Muñ oz et al, 2008).…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although amantadine was the result of a serendipitous discovery, increasing evidence points to the serotonergic system as a key player in the induction and expression of levodopa-induced dyskinesia (LID) in both patients with Parkinson's disease (Bonifati et al, 1994;Politis et al, 2014) and animal models of the disorder (Carta et al, 2007;Muñ oz et al, 2008). Studies in rat and primate models of Parkinson's disease have demonstrated that the serotonergic system is a major source of striatal levodopa-derived dopamine release (Carta et al, 2007;Muñ oz et al, 2008).…”
Section: Referencesmentioning
confidence: 99%
“…Aberrant release of dopamine derived from serotoninergic neurons seems to be instrumental for the emergence of LID in patients with Parkinson's disease. In fact, recent PET studies have shown that patients with dyskinesia have higher synaptic dopamine levels after L-DOPA treatment compared to non-dyskinetic subjects (de la Fuente-Fernandez et al, 2004;Politis et al, 2014). Administration of buspirone (a partial 5-HT1A receptor agonist) produced significant dampening of synaptic dopamine levels in these patients and attenuated the expression of LID (Politis et al, 2014).…”
Section: Referencesmentioning
confidence: 99%
“…[6][7][8][9] The above studies propose that serotonergic terminals in the degenerating striatum are responsible for mishandling exogenous levodopa and exacerbating dyskinesia in the animal model [10][11][12] and PD. 13 Accordingly, the presence of dyskinesia could be a reflection of serotonergic over dopaminergic terminals' activity. Nonetheless, the above mechanisms have not been fully understood in humans.…”
mentioning
confidence: 99%
“…The LED Total , LED Ldopa , and LED Dag doses were calculated in milligrams for each individual following the formulas 13 described in table e-1 on the Neurology ® Web site at Neurology.org. DD diagn was defined as the time from the date of the PD diagnosis at the movement disorders clinic and DD onset as the time since each individual first experienced a PD motor symptom.…”
mentioning
confidence: 99%
“…The cardinal pathological characteristic of PD is the progressive loss of dopaminergic neurons in the substantia nigra pars compacta [7], however, lines of evidence from in vivo molecular imaging research has demonstrated that PD pathology involves also non-dopaminergic systems such as the serotonergic [8][9][10]. Serotonergic pathology in PD has been associated with the development of tremor [11,12], dyskinesias [13][14][15] and various non-motor symptoms [16][17][18].…”
Section: Introductionmentioning
confidence: 99%